Statistically sound application of fiber push-out method for the study of locally non-uniform interfacial properties of SiC-SiC fiber composites - Hussey, A; De Meyere, R; Deck, C; Armstrong, DEJ; Zayachuk, Y (Elsevier, 2019)
Push-out tests were performed on SiC-SiC fiber composites with single- and multi-layered pyrolytic carbon fiber-matrix interphases. It is shown that experimental scatter is significant and a large number of tests is necessary in order to obtain statistically relevant values of interfacial shear strength. A difference between the regions of an individual fiber tow is observed, linked to local porosity. Interfacial debonding occurs along the boundary between the fiber and the first carbon layer, regardless of the structure of the interphase, and therefore interfacial shear strength is not directly linked to the structure of the interphase.